2022
DOI: 10.3390/ijerph191811496
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Likely Major Depressive Disorder among Medical Students in Alberta, Canada

Abstract: Background: Medical students are exposed to multiple factors during their academic and clinical studies that contribute to depression. Aims: This study aims to examine the prevalence and correlates of likely major depressive disorder (MDD) among medical students. Methods: This study utilized a descriptive cross-sectional design. Data were collected through a self-administered online survey, which included questions on sociodemographic characteristics and likely MDD using the PHQ-9. Data were analyzed using a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(103 reference statements)
0
2
0
2
Order By: Relevance
“…Also, many social life indicators, physical health, a history of psychological illness, and financial concerns make medical students more susceptible to depression [ 2 , 13 ]. Studies have identified several factors associated with higher odds of depression among medical students which include age, gender, physical health, social support, conflicts with teachers, personal events, finances, education, sleep, diet, socioeconomic status, family history, and emotional abuse [ 9 , 14 , 15 , 16 , 17 ]. In a descriptive cross-sectional study conducted among medical students in Canada, a high prevalence of major depressive disorder was reported among those who lacked sufficient social support from friends and family [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, many social life indicators, physical health, a history of psychological illness, and financial concerns make medical students more susceptible to depression [ 2 , 13 ]. Studies have identified several factors associated with higher odds of depression among medical students which include age, gender, physical health, social support, conflicts with teachers, personal events, finances, education, sleep, diet, socioeconomic status, family history, and emotional abuse [ 9 , 14 , 15 , 16 , 17 ]. In a descriptive cross-sectional study conducted among medical students in Canada, a high prevalence of major depressive disorder was reported among those who lacked sufficient social support from friends and family [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have identified several factors associated with higher odds of depression among medical students which include age, gender, physical health, social support, conflicts with teachers, personal events, finances, education, sleep, diet, socioeconomic status, family history, and emotional abuse [ 9 , 14 , 15 , 16 , 17 ]. In a descriptive cross-sectional study conducted among medical students in Canada, a high prevalence of major depressive disorder was reported among those who lacked sufficient social support from friends and family [ 15 ]. A multicenter cross-sectional study conducted in 12 Italian medical schools found factors associated with an increased risk of depressive symptoms, including being female, older age, poor economic status, lack of exercise, having relatives with psychiatric disorders, a personal chronic disease, negative perceptions of medical school, unsatisfying friendships with classmates and being worried about not measuring up to the profession [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pesquisas realizadas no Japão, mostraram que tanto para os residentes que sofrem SB, como para aqueles que não foram diagnosticados com a síndrome, a maior rede de apoio é constituída pelos próprios colegas do programa (MATSUO et al, 2021). Em estudantes de medicina canadenses, foi visto que a presença de suporte social previu a provável ausência de transtorno depressivo (DHANOA et al, 2022).…”
Section: Sb E Indicadores De Sofrimento/satisfação Emocional Com O Pr...unclassified
“…Pesquisas realizadas no Japão indicam que fatores como excesso de burocracia, horas de trabalho excessivas, baixa autonomia, problemas de comunicação no local de trabalho, queixas dos pacientes, competição entre pares e ansiedade sobre o futuro, estão associadas à prevalência de ambientes de trabalho que fomentam a SB (MATSUO et al, 2021). Segundo Dhanoa et al (2022), fatores ambientais associados a indicadores de depressão, são mais acentuados entre estudantes de medicina do gênero feminino. Além dos já mencionados, a exposição à morte e sofrimento, e a preparação insuficiente para enfrentar estas questões, além do abuso de estudantes (verbal, físico, assédio sexual e discriminação racial), fazem parte importante dos escores de satisfação com o ambiente, especialmente para as mulheres.…”
Section: Sb E Indicadores De Sofrimento/satisfação Emocional Com O Pr...unclassified